Supporting African American Student Success Through Prophetic Activism: New Possibilities for Public School–Church Partnerships. (January 2017) - Jordan, Diedria H.; Wilson, Camille M.
This article describes how African American students' success can be improved via the increased support of Black churches and their partnerships with public schools. Findings and implications from a comparative case study of two North Carolina churches that strive to educationally assist African American public school students are detailed. Both churches have outreach programs in local schools, and their activities indicate the value of faith-based partnerships embodying "prophetic activism" that benefits broader communities and empowers African Americans overall. We draw upon the study's findings to recommend partnership strategies for church and public educational leaders.